Bifunctional Electrocatalytic Activity of Boron‐Doped Graphene Derived from Boron Carbide. Issue 17 (25th June 2015) - Vineesh, Thazhe Veettil; Kumar, M. Praveen; Takahashi, Chisato; Kalita, Golap; Alwarappan, Subbiah; Pattanayak, Deepak K.; Narayanan, Tharangattu N.
<x xml:space="preserve">Abstract</x> A single material that can perform water oxidation and oxygen reduction reactions (ORR), also called bifunctional catalyst, represents a novel concept that emerged from recent materials research and that has led to applications in new‐generation energy‐storage systems, such as regenerative fuel cells. Here, metal/metal‐oxide free, doped graphene derived from rhombohedral boron carbide (B4C) is demonstrated to be an effective bifunctional catalyst for the first time. B4C, one of the hardest materials in nature next to diamond and cubic boron nitride, is converted and separated in bulk to form heteroatom (boron, B) doped graphene (BG, yield ≈7% by weight, after the first cycle). This structural conversion of B4C to graphene is accompanied by in situ boron doping and results in the formation of an electrochemically active material from a non‐electrochemically active material, broadening its potential for application in various energy‐related technologies. The electrocatalytic efficacy of BG is studied using various voltammetric techniques. The results show a four‐electron transfer mechanism as well as a high methanol tolerance and stability towards ORR. The results are comparable to those from commercial 20 wt% Pt/C in terms of performance. Furthermore, the bifunctionality of the BG is also demonstrated by its performance in water oxidation.